Optomechanical cooling by STIRAP-assisted energy transfer: an alternative route towards the mechanical ground state - Bijita Sarma; Thomas Busch; Jason Twamley (New Journal of Physics, 2020)
Standard optomechanical cooling methods ideally require weak coupling and cavity damping rates which enable the motional sidebands to be well resolved. If the coupling is too large then sideband-resolved cooling is unstable or the rotating wave approximation can become invalid. In this work we describe a protocol to cool a mechanical resonator coupled to a driven optical mode in an optomechanical cavity, which is also coupled to an optical mode in another auxiliary optical cavity, and both the cavities are frequency-modulated. We show that by modulating the amplitude of the drive as well, one can execute a type of STIRAP transfer of occupation from the mechanical mode to the lossy auxiliary optical mode which results in cooling of the mechanical mode. We show how this protocol can outperform normal optomechanical sideband cooling in various regimes such as the strong coupling and the unresolved sideband limit.